2015
DOI: 10.1152/ajplung.00237.2014
|View full text |Cite
|
Sign up to set email alerts
|

HER2 activation results in β-catenin-dependent changes in pulmonary epithelial permeability

Abstract: Finigan JH, Vasu VT, Thaikoottathil JV, Mishra R, Shatat MA, Mason RJ, Kern JA. HER2 activation results in ␤-catenindependent changes in pulmonary epithelial permeability. Am J Physiol Lung Cell Mol Physiol 308: L199 -L207, 2015. First published October 17, 2014; doi:10.1152/ajplung.00237.2014.-The receptor tyrosine kinase human epidermal growth factor receptor-2 (HER2) is known to regulate pulmonary epithelial barrier function; however, the mechanisms behind this effect remain unidentified. We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…The analysis of phenotype transit and signaling molecular indicated that HER2 may function through upregulation of β‐catenin and inhibition of SMAD2/3 complex activation. The functional connection among HER2, β‐catenin, and SMAD3 was supported with the evidence that HER2 and β‐catenin are physically associated . Immunoprecipitation of HER2 in normal and transformed epithelial cells was coimmunoprecipitated with the cadherin‐catenin complex, revealing a HER2 and β‐catenin in association with the basal condition .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The analysis of phenotype transit and signaling molecular indicated that HER2 may function through upregulation of β‐catenin and inhibition of SMAD2/3 complex activation. The functional connection among HER2, β‐catenin, and SMAD3 was supported with the evidence that HER2 and β‐catenin are physically associated . Immunoprecipitation of HER2 in normal and transformed epithelial cells was coimmunoprecipitated with the cadherin‐catenin complex, revealing a HER2 and β‐catenin in association with the basal condition .…”
Section: Discussionmentioning
confidence: 61%
“…Immunoprecipitation of HER2 in normal and transformed epithelial cells was coimmunoprecipitated with the cadherin‐catenin complex, revealing a HER2 and β‐catenin in association with the basal condition . The connection between HER2 and SMAD3 independent of TGF‐β receptor might be regulated through β‐catenin/Smad3 colocalization …”
Section: Discussionmentioning
confidence: 99%
“…HER2 has no known ligand, yet partners with other HER family members. For example, we have previously identified that HER2 dimerizes with HER3 after HER3 binding with the ligand neuregulin (NRG)-1, which leads to HER2-dependent increases in pulmonary epithelial permeability (11,12), and the NRG-1-HER2/3 signaling cascade participates in the pathogenesis of acute lung injury and the acute respiratory distress syndrome (7,8,11). Although HER2 is known to participate in epithelial barrier dysfunction in air-liquid interface (ALI), it has been unstudied in models of CS exposure.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Generally, HER receptor activation occurs rapidly after ligand binding (11,12). Given this, we next sought to determine if transient, acute CS induced activation of HER2 in cultured pulmonary epithelial cells.…”
Section: Transient Cs Activates Her2 Her3 and Egfr In Pulmonary Epimentioning
confidence: 99%
See 1 more Smart Citation